Cancún, une ville caribéenne : le tourisme au cœur des séparations sociales et spatiales - Jaime Aragón Falomir (Études Caribéennes)
Cancún, a major tourist destination in the Mexican Caribbean, exemplifies the contradictions of global capitalism, where extreme wealth coexists with deep social inequality. As a semi-peripheral global city, it reflects the disparities observed in major metropolitan centers but within a tourism-driven economy. This article explores how corporate power shapes urban space, reinforcing socio-spatial segregation and limiting access to resources for local residents. Drawing from theories of globalization, neoliberalism, and postcolonialism, this study highlights the intersection of economic power, social exclusion, and the commodification of urban life in Cancún.